Simultaneous estimation of PD, T1, T2, T2*, and ∆B0 using magnetic resonance fingerprinting with background gradient compensation. Issue 4 (13th November 2018) - Hong, Taehwa; Han, Dongyeob; Kim, Dong‐Hyun
Abstract : Purpose: This study aims to estimate PD, T1, T2, T2 *, and Δ B0 simultaneously using magnetic resonance fingerprinting (MRF) with compensation of the linearly varying background field. Methods: MRF based on fast imaging with steady‐state precession (FISP) and multi‐echo spoiled gradient (SPGR) schemes are alternatively used, which encode T2 and T2 *, respectively. Simulations are performed to determine the appropriate ratio of the FISP and SPGR sections with respect to the T2 and T2 * accuracy. Additionally, background field inhomogeneity (Gz ) compensation using z‐shim gradients are incorporated into the SPGR section and the dictionary. The background field compensation is tested in the phantom experiment under well‐shimmed and poor‐shimmed conditions. An in vivo experiment is performed and the estimated parameters are compared before and after Gz compensation. Results: The T1, T2, and T2 * values from the phantom results are in good agreement with the reference methods under well‐shimmed condition. The underestimated T2 and T2 * values under poor‐shimmed condition are recovered by Gz compensation and the parameters are also in good agreement with the reference methods. In the human brain, T2 and T2 * values are restored by Gz compensation in regions where the magnetic field is particularly inhomogeneous, such as near the sinus and ear canals. Conclusions: The proposed FISP and SPGR combined MRF provides a simultaneous estimation of PD, T1, T2, T2 *, and Δ B0 . By incorporating field inhomogeneity as a gradient term into both the sequence and dictionary, T2 and T2 * values can be restored where field inhomogeneity exists.